Optimum Production Planning by the Maximum Principle - Hwang, C. L.; Fan, L. T.; Erickson, L. E. (Management Science, 1967)
This study deals with the problem of optimum production planning with certainty in sales forecasting. The objective to be minimized is the sum of the costs derived from holding inventories, stockouts, and the deviation of the production rate from the optimal rate for the plant. Pontryagin's maximum principle is employed to obtain an optimal production policy.